Heterogeneous spillover effects of children's education on parental mental health - Jakob Everding (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2019)
Despite extensive research on nonmarket returns to education, direct and spillover effects on mental health are widely unstudied. This study is the first to analyze heterogeneous intergenerational effects of children's education on parents' mental health. Given ambiguous theoretical implications, I explore potential mechanisms empirically. Using Survey on Health, Ageing and Retirement in Europe (SHARE) data, I estimate IV regressions, exploiting countrylevel variation in compulsory schooling reforms. Increasing children's education reduces parents' long-term probability of developing depression. Fathers and more educated sons drive this beneficial effect. Since mental illness is frequently undiagnosed, the findings may help improve elderly-specific health care provision.
Keywords: I12; I26; J14; J24; C36; 330; compulsory schooling reforms; depression; old age; instrumental variable regression; intergenerational spillover